Rhetorical Structures of Introduction Sections in Sinta-Indexed Journals - Lisa Wijaya; Barli Bram (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
This discourse study examines the rhetorical structures of RA introductions in Sinta 1 indexed ELT journals by implementing the Swales’ (2004) CARS model as the framework for analysis. A corpus consisting of 36 RA introductions was randomly collected from three SINTA 1 indexed journals, namely TEFLIN, SiELE, and IJAL, in 2019-2021. The analysis was done by using top-down analysis. The findings of the study indicated that all three moves, i.e., Move 1 Establishing a territory, Move 2 Establishing a niche, and Move 3 Presenting the present work, appeared in the introduction section across three journals. Although not all authors presented the moves and steps in appropriate sequences, the structures of moves and steps found in the corpus data were based on Swales’ CARS model. It is highly suggested that EFL students follow the Swales’ CARS model in writing an introduction.